2020
DOI: 10.1136/archdischild-2020-320372
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal increases in childhood depression symptoms during the COVID-19 lockdown

Abstract: ObjectiveThere has been widespread concern that so-called lockdown measures, including social distancing and school closures, could negatively impact children’s mental health. However, there has been little direct evidence of any association due to the paucity of longitudinal studies reporting mental health before and during the lockdown. This present study provides the first longitudinal examination of changes in childhood mental health, a key component of an urgently needed evidence base that can inform poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
217
7
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(250 citation statements)
references
References 28 publications
16
217
7
10
Order By: Relevance
“…Compared to other studies with pre-COVID-19 and postlockdown measurement, the finding of an increase in depressive symptoms is consistent with one previous study (Bignardi et al, 2020), but it differs from another which found no change in depressive F I G U R E 5 Impact of being in the 'high-risk' category of potential moderators of the effects of the pandemic on the increase in symptoms from pre to post-pandemic F I G U R E 6 Rates of clinically significant child and mother symptoms of depression comparing those in the most deprived IMD, Indices of Multiple Deprivation Index quintile with the remainder WRIGHT ET AL.…”
Section: Discussionsupporting
confidence: 90%
“…Compared to other studies with pre-COVID-19 and postlockdown measurement, the finding of an increase in depressive symptoms is consistent with one previous study (Bignardi et al, 2020), but it differs from another which found no change in depressive F I G U R E 5 Impact of being in the 'high-risk' category of potential moderators of the effects of the pandemic on the increase in symptoms from pre to post-pandemic F I G U R E 6 Rates of clinically significant child and mother symptoms of depression comparing those in the most deprived IMD, Indices of Multiple Deprivation Index quintile with the remainder WRIGHT ET AL.…”
Section: Discussionsupporting
confidence: 90%
“…In the literature, emotional and overall discomfort problems resulting from the lockdown period, the school closure and poor socialization are becoming increasingly evident also in the pediatric population. The results of the studies show that the nature and extent of this impact depend on various vulnerability factors such as developmental age, pre-existing physical and mental health conditions, being economically disadvantaged, but also being quarantined due to infection or risk of infection [ 16 , 180 , 181 , 182 ].…”
Section: Resultsmentioning
confidence: 99%
“…Where studies have been able to combine pre-and early-pandemic data on psychopathology symptoms, results are limited and conflicting. One study reported increases in anxiety levels pre-to earlypandemic (Magson et al, 2021), while other studies have reported decreases (Widnall et al, 2020) or stability in anxiety symptoms (Barendse et al, 2021;Bignardi et al, 2020).…”
Section: Decrease In Anxiety Symptoms and Less Overall Symptoms Than Expectedmentioning
confidence: 99%